Human CD49a+ Lung Natural Killer Cell Cytotoxicity in Response to Influenza A Virus - Cooper, Grace E.; Ostridge, Kristoffer; Khakoo, Salim I.; Wilkinson, Tom M. A.; Staples, Karl J. (Frontiers in Immunology, 2018)
Influenza A virus (IAV) is a major global public health burden due to its routine evasion of immunisation strategies. Natural Killer (NK) cells are innate cytotoxic cells with important antiviral activity in the human body, yet the function of these cells in the control of IAV infection is unclear. The aim of this study was to determine the role of lung NK cell cytotoxic responses to IAV. Human lung explants were infected ex vivo with IAV and lung NK cell activation was analysed by flow cytometry. Cytotoxic responses of NK cell subsets against IAV-infected macrophages were measured by flow cytometry and ELISA. Despite reports of hypofunctionality in the pulmonary environment, human lung-associated NK cells responded rapidly to ex vivo IAV infection, with upregulation of surface CD107a 24 h post-infection. The lung NK cell phenotype is similar in maturity and differentiation to NK cells of the peripheral blood but a unique CD56brightCD49a+CD103+CD69+ NK cell population was identified in the lung, indicating NK cell residency within this organ. In response to ex vivo IAV infection a greater proportion of resident CD56brightCD49a+ NK cells expressed surface CD107a compared to CD56brightCD49a- NK cells, suggesting a hyperfunctional NK cell population may be present within human lung tissue and could be the result of innate immunological training. Furthermore NK cells provided significant anti-viral, cytotoxic activity following contact with influenza infected cells, including the production and release of IFN-γ and Granzyme-B resulting in macrophage cell death. These results suggest that a resident, memory NK cell population are present in the human lung and may provide early and important control of viral infection. A greater understanding of this resident mucosal population may provide further insight into the role of these cells in controlling viral infection and generating appropriate adaptive immunity to IAV.